Myeloid sarcoma: a report of four cases at unusual sites - Siraj, Fouzia; Kaur, Manveen; Dalal, Varsha; Khanna, Ashima; Khan, Afaq Ahmad (GMS German Medical Science, 2017)
Background: Myeloid sarcoma (MS) or granulocytic sarcoma is a rare tumor consisting of myeloid blasts with or without maturation occurring at anatomic sites other than the bone marrow. MS can involve any organ system but shows a predilection for skin, bone, and soft tissues of head and neck region.Case report: We report four cases of MS occurring at unusual sites, out of which three were de novo and one was associated with acute myeloid leukemia (AML).Conclusion: Although MS is associated with AML, it can rarely present without any existent hematologic disease. Differential diagnosis of a soft tissue mass should include MS even in the absence of leukemia. Establishment of the correct diagnosis depends on morphologic, histochemical, and immunohistochemical examination.